Anesthetic management of a neonate with an intrapericardial teratoma: a case report. Issue 12 (17th September 2020) - Lu‐Boettcher, Ying E.; Koppera, Prabhat; Riegger, Lori Q.
Abstract: Intrapericardial teratomas can exert mass effect on the cardiovascular and respiratory system. Adequate volume resuscitation and anticipation of cardiopulmonary collapse is paramount in the management of these patients in the operating room. Abstract : Intrapericardial teratomas can exert mass effect on the cardiovascular and respiratory system. Adequate volume resuscitation and anticipation of cardiopulmonary collapse is paramount in the management of these patients in the operating room.